2000
DOI: 10.1007/s002100000274
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of caffeic acid on α 1A -adrenoceptors to increase glucose uptake into cultured C 2 C 12 cells

Abstract: In an attempt to understand the antihyperglycemic action of caffeic acid, the myoblast C2C12 cells were employed to investigate the glucose uptake in the present study. Caffeic acid enhanced the uptake of radioactive glucose into C2C12 cells in a concentration-dependent manner. Similar effect of phenylephrine on the uptake of radioactive glucose was also observed in C2C12 cells. Prazosin attenuated the action of caffeic acid in a way parallel to the blockade of phenylephrine. Effect of caffeic acid on alpha1-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…Several phenolic compounds and flavonoid possess marked anti-diabetic activity (Hsu et al, 2000). In addition, caffeic acid, a phenolic compound, has been reported to increase glucose uptake in rat myocytes (Cheng and Liu, 2000). Our present results showed that Orthosiphon stamineus extract significantly reduced plasma glucose concentration in both normal and diabetic rats.…”
Section: Discussionmentioning
confidence: 63%
“…Several phenolic compounds and flavonoid possess marked anti-diabetic activity (Hsu et al, 2000). In addition, caffeic acid, a phenolic compound, has been reported to increase glucose uptake in rat myocytes (Cheng and Liu, 2000). Our present results showed that Orthosiphon stamineus extract significantly reduced plasma glucose concentration in both normal and diabetic rats.…”
Section: Discussionmentioning
confidence: 63%
“…It has antifungal, antiviral, anticarcinogenic, anti‐inflammatory, antioxidant and antidiabetic properties (Shahrzad, Hodgson, & Narumi, 2001). Caffeic acid has also been reported to increase glucose uptake in rat myocytes (Cheng & Liu, 2000). Quercetin is one of the most common flavonoids occurring mainly in glycosidic forms such as rutin (Havsteen, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK is also not secondary to changes in PKC activity despite PKC being implicated in ␣ 1 -adrenoceptor mediation of glucose uptake (12,29). The phorbol ester TPA (which activates conventional and novel PKC isoforms) did not phosphorylate AMPK, and downregulation of conventional and novel PKCs with long-term TPA (33) or the use of PKC inhibitors did not affect the ability of cirazoline (or AICAR) to phosphorylate AMPK, suggesting that PKCs are not involved in phosphorylation of AMPK (PKC inhibition was also ineffective in inhibiting AICAR activation of AMPK in rat papillary muscle [45]).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are blocked by guanethidine but not by adrenal medullation, showing that norepinephrine and not epinephrine mediates this response (24). Other studies performed in vivo and in vitro show that ␣-and ␤-adrenoceptor (12,15,(25)(26)(27)(28)(29) activation increases glucose uptake in skeletal muscle via an insulin-independent pathway. Hence it is likely that circulating epinephrine has vastly different actions on glucose uptake as opposed to focally released norepinephrine at the synaptic clefts, which can reach high concentrations.…”
mentioning
confidence: 91%